2021
DOI: 10.1002/pbc.28860
|View full text |Cite
|
Sign up to set email alerts
|

Clear cell sarcoma of the kidney in Austrian children: Long‐term survival after relapse

Abstract: Introduction Clear cell sarcoma of the kidney (CCSK) is a rare malignant childhood renal tumour. Recently, the central nervous system (CNS) was found to be the most frequent site of relapse associated with a poor outcome. Optimal treatment strategies are scarce. Patients and Methods Retrospective data analysis of all Austrian children with CCSK. They were enrolled in the Austrian‐Hungarian Wilms Tumour Study (AHWTS) 1989, the SIOP93‐01 or the SIOP2001 study between 1990 and 2019. Demographic, diagnostic, treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
(72 reference statements)
0
7
0
Order By: Relevance
“…We finally included 16 studies in the research (8 studies for each treatment approach group), for a total of 715 patients, 367 in the SIOP group and 348 in the COG group. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] All studies are reported in ►Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We finally included 16 studies in the research (8 studies for each treatment approach group), for a total of 715 patients, 367 in the SIOP group and 348 in the COG group. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] All studies are reported in ►Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…11,19 High risk for selective reporting was associated with three studies. 8,10,15 Furthermore, 30% of the studies were associated with low risk, 50% with high risk for other types of bias, 7,8,[11][12][13][14][15]17 and the remaining 20% with unclear risk for other bias 18,20 (►Fig. 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Rarity represents the greatest barrier to advances in the diagnosis and treatment of CCSK. There have been several follow-up clinical studies on CCSK relapse (5,(16)(17)(18)32). Most of them were single-center observations with small samples.…”
Section: Relapse-related Factors In the Relapse Groupmentioning
confidence: 99%
“…A combined SIOP and Associazione Italiana Ematologia Oncologia Pediatrica (AIEOP) study showed that relapse occurs in about 16% of patients (5). Several follow-up clinical studies on relapse of CCSK showed that relapse patients who receive only primary treatment with resection + chemotherapy + radiotherapy exhibit a poor prognosis due to the absence of effective treatment standards for relapsed CCSK (16)(17)(18). These were mostly single-center studies with a small sample size and no analysis of relapse-related factors.…”
Section: Introductionmentioning
confidence: 99%